Time Series Decomposition as a Method of Measuring Capital Markets Convergence - Żukowski, Rafał (Olsztyn Economic Journal, 2020)
The aim of the article is to present time series decomposition as a method of measuring capital markets convergence. As an example, convergence of two different sets of markets are measured using this methodology. On the basis of this research, it has been established that time series decomposition of the market indices can prove or reject a hypothesis of moving indices in similar directions over a period of time.